Automatic Daily Scheduling System Using Cron Jobs for Handicraft Business Management - Terecia, Lidia; Kosasi, Sandy; David, David (CORISINDO 2025, 2025)
Ensuring accurate stock information remains a challenge for handicraft business managers when sales data from physical stores and e-commerce platforms are not updated simultaneously. Previous studies have addressed stock synchronization but have yet to employ scheduling mechanisms for delivering daily stock summaries integrated with sales data from both sources. This study developed an automated scheduling system using a cron job to record and summarize daily stock movements, utilizing Shopee API integration to ensure data consistency between the physical store and the online platform. The Reorder Point concept was applied to determine restocking thresholds, while the Twilio API was used to send stock summaries to managers via WhatsApp. The system was implemented using the Extreme Programming method to accelerate adaptation to user requirements. The results indicated that the system consistently provided daily stock reports, maintained data consistency across platforms, and supported procurement decision-making. This approach offers a novelty by combining automated stock synchronization and scheduled stock report distribution within a single integrated system.